Assessment of erosion, deposition and fuel retention in the JET-ILW divertor from ion beam analysis data. (August 2017) - Catarino, N.; Barradas, N.P.; Corregidor, V.; Widdowson, A.; Baron-Wiechec, A.; Coad, J.P.; Heinola, K.; Rubel, M.; Alves, E.
Abstract: Post-mortem analyses of individual components provide relevant information on plasma-surface interactions like tungsten erosion, beryllium deposition and plasma fuel retention with divertor tiles via implantation or co-deposition. Ion Beam techniques are ideal tools for such purposes and have been extensively used for post-mortem analyses of selected tiles from JET following each campaign. In this contribution results from tiles removed from the JET ITER-Like Wall (JET-ILW) divertor following the 2013–2014 campaign are presented. The results summarize erosion, deposition and fuel retention along the poloidal cross section of the divertor surface and provide data for comparison with the first JET-ILW campaign, showing a similar pattern of material migration with the exception of Tile 6 where the strike point time on the tile was ∼ 4 times longer in 2013–2014 than in 2011–2012, which is likely to account for more material migration to this region. The W deposition on top of the Mo marker coating of Tile 4 shows that the enrichment takes place at the strike point location.